Journeys of violence: Trajectories of (im-)mobility and migrants' encounters with violence in European border spaces - Rahel Lorenz; Benjamin Etzold (Comparative Population Studies (CPoS), 2022)
On their journeys to and through Europe, refugees and other migrants are commonly subjected to violence in its multifaceted forms. We argue that these "journeys of violence" are a direct effect of a fundamentally uneven and asymmetric global mobility regime that creates frictions and fragmentations in the European border space and beyond. Our argument is based on: (1) a state-of-the-art literature review on refugees' mobilities towards Europe and new patterns of involuntary immobilisation through border regimes, (2) a secondary analysis of recent quantitative data from the Socio-Economic Panel (SOEP), which includes a large data set on refugee's journeys to Germany, and (3) original qualitative interviews that were conducted with migrants in Germany and Bosnia-Herzegovina. We will first show that mobility in the context of violence is highly selective and that trajectories of mobility significantly depend on mobility capital. Second, we consider the fortification of European borders and the externalisation of control regimes as facets of structural violence and demonstrate their effects on refugees' mobility, namely the fragmentation of journeys and the systemic production of situations of protracted immobility at multiple border sites. Third, we provide insights into refugees' exposure to and experiences of direct violence on their journeys, which must be understood as immediate consequences of the structurally violent conditions that govern their mobility and the cultural violence of delegitimising and illegalising refugees' movements.
urn:nbn:de:bib-cpos-2022-09en4
Keywords: 300; Refugee journeys; Encounters with violence; European border regime; Fragmentation; Immobilisation; Stratified mobility